PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN DI LINGKUNGAN KANTOR PUSAT UNIVERSITAS JEMBER - Prasetiyo, Budi (BISMA: Jurnal Bisnis dan Manajemen, 2017)
Abstract: Employee contribution becomes important when it is done with effective action and right behavior. Not only the amount of effort but also the direction of the business. The nature, effort or willingness to work as well as the various things that constitute organizational support is very important for the success of employee performance. In this study, the author tries to analyze the problems faced by the administrative staff of Jember University (UNEJ). Empirical tests were conducted on 115 administrative employees to obtain data on organizational culture and leadership style that has been enough to give hope to the administrative staff. Analyzer used in this research is Structural Equation Model (SEM). From the results of model testing, it can be concluded that organizational culture and leadership style have a positive effect on job satisfaction, leadership style positively affect the organizational culture. Organizational culture, leadership style, and job satisfaction have a positive effect on employee performance. To improve the performance of administrative employees, especially the dimensions of cost control and self-reliance initiatives, it requires a bureaucratic leadership style and autocratic leadership style in an open and process-oriented organizational culture system as an effort to improve employee job satisfaction.Keywords: Organizational Culture, Leadership Style, Job Satisfaction, and Employee Performance